2012
DOI: 10.2500/ajra.2012.26.3776
|View full text |Cite
|
Sign up to set email alerts
|

Rhinosinusitis-Related Quality of Life during Pregnancy

Abstract: Rhinosinusitis-specific QOL is lower in the third trimester of pregnancy in comparison with the second trimester and also in comparison with nonrhinosinusitis patients. Increased awareness may enhance the QOL of pregnant patients, prevent OSA, and thereby positively influence the outcome of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…310 Rhinitis in pregnancy impacts negatively on quality of life, especially during the third trimester and women with pre-existing allergic rhinitis are more severely affected. 314 Informing the patient that pregnancyinduced rhinitis is a self-limiting condition is often reassuring.…”
Section: Frequent Monitoring Visits For Slitmentioning
confidence: 99%
“…310 Rhinitis in pregnancy impacts negatively on quality of life, especially during the third trimester and women with pre-existing allergic rhinitis are more severely affected. 314 Informing the patient that pregnancyinduced rhinitis is a self-limiting condition is often reassuring.…”
Section: Frequent Monitoring Visits For Slitmentioning
confidence: 99%
“…Die Lebensqualität der Schwangeren zeigte eine erhebliche Beeinträchtigung durch die Symptomatik, welche im 3. Trimenon als besonders stark empfunden wurde [11].…”
Section: Inzidenz and Klinikunclassified
“…This result is more compatible with changes in nasal resistance during pregnancy. Gilbey et al conducted a cross‐sectional study with 76 pregnant women to assess rhinosinusitis‐related quality of life via the 22‐item Sino‐Nasal Outcome Test (SNOT‐22). They reported that the mean item score was significantly higher for the third trimester compared to the second trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal congestion that is not present before pregnancy represents a distinct clinical entity known as “pregnancy‐related rhinitis.” This condition has been defined by Ellegård and Karlson as “nasal congestion present in the last 6 or more weeks of pregnancy without other signs of respiratory tract infection and with no known allergic cause, disappearing completely within 2 weeks after delivery.” In previous studies, this condition was reported to affect up to 20% to 40% of women in all trimesters of pregnancy . It is a common belief of the public and medical doctors that this condition severely reduces quality of life in pregnant women . Nasal obstruction during pregnancy has been suggested to cause snoring and obstructive sleep apnea (OSA).…”
mentioning
confidence: 99%
See 1 more Smart Citation